1998
DOI: 10.1063/1.476251
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of the isotope effects on the fluorescence excitation spectrum of 5-aminotropolone

Abstract: A combined ab initio+nuclear dynamics study is performed to theoretically analyze the intramolecular H-atom transfer process in 5-aminotropolone in both the ground (S0) and first excited (S1) singlet electronic states. A complete active space self-consistent field (CASSCF) method is used to optimize the geometries. Energies are then corrected through the second order Mo/ller–Plesset perturbation theory. These results are used to build up reduced bidimensional energy surfaces so that the nuclear wave functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…twisting coordinate, evidencing a kind of cooperative motion involving the two coordinates. A similar behavior has been observed in tropolone, [28][29][30][31] where it has been shown that the barrier to intramolecular hydrogen atom transfer from the -OH to the C v O group is substantially reduced by excitation of -C v C-stretching modes in the seven-membered ring.…”
Section: ͑2͒supporting
confidence: 77%
“…twisting coordinate, evidencing a kind of cooperative motion involving the two coordinates. A similar behavior has been observed in tropolone, [28][29][30][31] where it has been shown that the barrier to intramolecular hydrogen atom transfer from the -OH to the C v O group is substantially reduced by excitation of -C v C-stretching modes in the seven-membered ring.…”
Section: ͑2͒supporting
confidence: 77%
“…The computational study of hydrogen bonds and proton transfers in their ground states has been sufficiently extensive that there exists a general understanding of the errors incurred by the use of any particular method. For example, it is widely recognized that enlargements of basis set lead to higher transfer barriers, while electron correlation reduces the barrier. Moreover, there is every indication that most of the popular means of including correlation, i.e., MP2, MP4, QCISD, coupled cluster, etc., are in fair agreement concerning transfer barriers. Transfers in excited states, on the other hand, have been studied far less extensively, so that there is no consensus yet as to which methods are most appropriate and accurate. Indeed, this issue is not limited to the proton transfer problem; computational methodology for excited states of molecular systems is generally much less mature than for closed-shell ground electronic states.…”
Section: Methodological Investigationsmentioning
confidence: 99%
“…Introduction of asymmetry by substituting one D atom into the NH 2 group quenched proton tunneling in the ground state . These experimental findings have been supported by a combined ab initio + nuclear dynamic study . In 5-hydroxytropolone, the two in-plane orientations of the 5-OH substituent produced two isomers, syn and anti, relative to the 2-OH. , It has been postulated that there are two reaction coordinates for the syn-anti photoisomerization; these coordinates involve 2-OH tunneling and 5-OH torsion. Nishi et al have clarified the coupling as regards the internal rotation of the methyl group and the intramolecular proton transfer. , They showed a drastic decrease in the tunneling splitting of the zero-vibrational level, compared to that of TRN.…”
Section: Introductionmentioning
confidence: 91%
“…4 These experimental findings have been supported by a combined ab initio + nuclear dynamic study. 9 In 5-hydroxytropolone, the two inplane orientations of the 5-OH substituent produced two isomers, syn and anti, relative to the 2-OH. 5,6 It has been postulated that there are two reaction coordinates for the syn-anti photoisomerization; these coordinates involve 2-OH tunneling and 5-OH torsion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation